Cinema, philosophy, Bergman on film as philosophy - Livingston, Paisley, 1951- (Oxford : Oxford University Press, 2009)
Can cinema be a medium for philosophy? Paisley Livingston explores the philosophical value of cinema. As a case-study for his intentionalist theory of authorship and interpretation he focuses on Ingmar Bergman's cinematic explorations of motivated irrationality, inauthenticity, and self-knowledge.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Bergman, Ingmar, -- 1918-2007 -- Criticism and interpretation; Bergman, Ingmar, -- 1918-2007 -- Philosophy; Motion pictures -- Philosophy; Philosophy in motion pictures